wo new varieties of buckwheat in Slovenia - Luthar, Zlata (Anali PAZU, 2022)
Cancer patients on chemotherapy treatment may have several symptoms. In the study Mobile application for patients with breast cancer treated with chemotherapy and targeted therapy, patients reported symptoms by means of the mobile application. Patient could report 50 symptoms. A patient having a specific symptom, defines a severity (mild, moderate or severe) and its duration. We performed analysis on 16 patients for the first cycle of chemotherapy. The median follow-up was 3 weeks. The most prevalent symptoms were fatigue (75%), dry mouth, headache, redness of the face (56%), myalgia, hoarsenes, heartburn, meteorism (31%), obstipation, diarrhoea (25%) and alopecia (44%). The majority of symptoms were mild or moderate intensity, and short lasting (less then 4 days). Reporting symptoms is of great help for the treating oncologist for better symptom treatment.